Active energy ray-curable adhesive composition, adhesive composition for polarizing plate, adhesive for polarizing plate, polarizing plate

JP7631987B2Active Publication Date: 2025-02-19MITSUBISHI CHEM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021057404
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-02-19
Estimated Expiration
2041-03-30

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、保護フィルムがアクリル系フィルム、環状オレフィン系フィルムであっても、偏光子と保護フィルムとの間の接着力に優れる接着剤が得られる活性エネルギー線硬化性接着剤組成物;前記活性エネルギー線硬化性接着剤組成物を用いた偏光板用接着剤組成物;偏光板用接着剤;及び偏光板が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631987000005
    Figure 0007631987000005
  • Figure 0007631987000001
    Figure 0007631987000001
  • Figure 0007631987000002
    Figure 0007631987000002
Patent Text Reader

Abstract

To provide: an active energy ray-curable adhesive composition capable of obtaining an adhesive having excellent adhesive force between a polarizer and a protective film even when the protective film is an acrylic film or a cyclic olefin-based film; an adhesive composition for a polarizing plate using the active energy ray-curable adhesive composition; an adhesive for a polarizing plate; and a polarizing plate.SOLUTION: There is provided an active energy ray-curable adhesive composition which comprises an epoxy compound (A), an ethylenically unsaturated compound (B), a photopolymerization initiator (C) and a silane coupling agent (D) and does not contain an oxetane compound, wherein the epoxy compound (A) contains an aliphatic epoxy compound (A1) and an aromatic epoxy compound (A2), the photopolymerization initiator (C) contains a photocationic polymerization initiator (C1) and a photo-radical polymerization initiator (C2) and a content of the photo-radical polymerization initiator (C2) is less than 1 pt.wt. based on the total 100 pts.wt. of the epoxy compound (A) and the ethylenically unsaturated compound (B).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active energy ray-curable adhesive composition, an adhesive composition for polarizing plates, an adhesive for polarizing plates, and a polarizing plate. [Background technology]

[0002] A polarizing plate formed by laminating a polarizer and a protective film may be used in a liquid crystal display device. Liquid crystal display devices are widely used as image display devices such as liquid crystal televisions, computer displays, mobile phones, and digital cameras. Such liquid crystal display devices are configured such that polarizing plates are laminated on both sides of a glass substrate in which liquid crystal is sealed, and various optically functional films such as retardation plates are laminated thereon as necessary.

[0003] A polarizing plate is generally constructed by laminating a protective film on at least one surface, preferably both surfaces, of a polarizer made of a polyvinyl alcohol (PVA)-based film. Here, as the polarizer, a uniaxially stretched PVA-based film is widely used, which is a PVA-based film formed by using a PVA-based resin with a high degree of saponification, in which a dichroic material such as iodine is dispersed and adsorbed, and preferably further crosslinked by a crosslinking agent such as boric acid. Since such a polarizer is a uniaxially stretched PVA-based film, it is prone to shrinkage under high humidity conditions, and a protective film is laminated to the polarizer in order to compensate for moisture resistance and strength.

[0004] As such protective films, thermoplastic resins such as cellulose resins, polycarbonate resins, cyclic polyolefin resins, (meth)acrylic resins, and polyester resins are used because they have excellent transparency, mechanical strength, thermal stability, moisture blocking properties, isotropy, etc., and in particular, protective films made of triacetyl cellulose (TAC) resins are widely used. These protective films are attached to the polarizer with an adhesive. As such an adhesive, an aqueous solution of a PVA-based resin, particularly an aqueous solution of a PVA-based resin mainly composed of a highly saponified PVA-based resin similar to that of the polarizer, is preferably used in terms of adhesion to the polarizer having a hydrophilic surface.

[0005] In recent years, there has been a demand for thinner polarizing plates, and acrylic films, cyclic olefin (COP) films, and polyester (PET) films have begun to be used in place of the TAC films that have been the most commonly used protective films up until now.

[0006] However, these protective films replacing TAC films have problems such as difficulty in firmly bonding to polarizers with conventional PVA-based adhesives and the resulting polarizing plate having poor appearance. This is because acrylic films and cyclic olefin films are more hydrophobic than TAC films and have low moisture permeability, so water cannot be dried sufficiently. Therefore, various adhesives suitable for bonding protective films such as acrylic films, cyclic olefin films, and PET films have been developed as alternatives to PVA-based adhesives (for example, Patent Documents 1 and 2).

[0007] Patent Document 1 proposes an adhesive composition for polarizing plates that contains an epoxy resin, an acrylic monomer, a photoacid generator, and a photopolymerization initiator. Patent Document 2 proposes an active energy ray-curable adhesive composition containing an oxetane compound, an epoxy compound, an ethylenically unsaturated compound, and a photopolymerization initiator. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2014-37477 A [Patent Document 2] JP 2020-105265 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, there is room for improvement in the adhesive strength between various protective films and polarizers in the adhesive compositions for polarizing plates of Patent Documents 1 and 2. In particular, when the protective film is an acrylic film or a cyclic olefin film, the adhesive strength between the protective film and the polarizer is insufficient. In addition, in recent years, usage environments have become more diverse and high durability is required, but conventional adhesives such as those described in Patent Documents 1 and 2 cannot provide sufficient adhesive strength or durability between a protective film and a polarizer. In particular, there is still room for improvement in the adhesiveness between a protective film such as an acrylic film or a cyclic olefin film and a polarizer.

[0010] Furthermore, in recent years, polarizing plates in which both sides of a polarizer are protected with various films via adhesives are required to have various durability characteristics. Therefore, in consideration of the actual display usage environment, it is natural that the quality does not deteriorate over a long period of time, and it is particularly required to have measures to prevent deterioration of adhesive performance and polarizer deterioration under high temperature and high humidity.

[0011] Therefore, the present invention aims to provide an active energy ray-curable adhesive composition that can provide an adhesive with excellent adhesion between a polarizer and a protective film, even if the protective film is an acrylic film or a cyclic olefin film; an adhesive composition for polarizing plates that uses the active energy ray-curable adhesive composition; an adhesive for polarizing plates; and a polarizing plate. [Means for solving the problem]

[0012] As a result of extensive research, the present inventors have found that an active energy ray-curable adhesive composition containing an epoxy compound (A), an ethylenically unsaturated compound (B), a photopolymerization initiator (C), and a silane coupling agent (D), which does not contain an oxetane compound, contains an aliphatic epoxy compound (A1) and an aromatic epoxy compound (A2) as the epoxy compound (A), and the photopolymerization initiator (C) contains a photocationic polymerization initiator (C1) and a photoradical polymerization initiator (C2), and contains a specific small amount of the photoradical polymerization initiator (C2), has excellent adhesive strength even when the protective film is an acrylic film or a cyclic olefin film, and have completed the present invention.

[0013] The present invention has the following aspects. [1] An active energy ray-curable adhesive composition comprising an epoxy compound (A), an ethylenically unsaturated compound (B), a photopolymerization initiator (C), and a silane coupling agent (D); the active energy ray-curable adhesive composition does not contain an oxetane compound; the epoxy compound (A) comprises an aliphatic epoxy compound (A1) and an aromatic epoxy compound (A2); the photopolymerization initiator (C) comprises a photocationic polymerization initiator (C1) and a photoradical polymerization initiator (C2); and the content of the photoradical polymerization initiator (C2) is less than 1 part by weight per 100 parts by weight of the total of the epoxy compound (A) and the ethylenically unsaturated compound (B). [2] The active energy ray-curable adhesive composition according to [1], wherein the content of the aliphatic epoxy compound (A1) is greater than the content of the aromatic epoxy compound (A2). [3] The active energy ray-curable adhesive composition according to [1] or [2], wherein the aromatic epoxy compound (A2) is substantially free of bisphenol S type, naphthalene type, or resorcinol type aromatic epoxy compounds. [4] The active energy ray-curable adhesive composition according to any one of [1] to [3], wherein the ethylenically unsaturated compound (B) is an alkyl(meth)acrylate having 1 to 4 carbon atoms. [5] The active energy ray-curable adhesive composition according to any one of [1] to [4], wherein the content of the ethylenically unsaturated compound (B) is greater than the content of the epoxy compound (A). [6] An adhesive composition for polarizing plates, comprising the active energy ray-curable adhesive composition according to any one of [1] to [5]. [7] An adhesive for polarizing plates, which is a cured product of the adhesive composition for polarizing plates described in [6]. [8] A polarizing plate comprising a polarizer, a protective film, and an adhesive layer for bonding the polarizer and the protective film together, the adhesive layer being made of the adhesive for polarizing plates according to [7]. [9] The polarizing plate according to [8], wherein the protective film is at least one selected from the group consisting of acetyl cellulose-based films, acrylic-based films, cyclic olefin-based films, and polyethylene terephthalate-based films. Effect of the Invention

[0014] According to the present invention, there are provided an active energy ray-curable adhesive composition that can provide an adhesive having excellent adhesion between a polarizer and a protective film, even when the protective film is an acrylic film or a cyclic olefin film; an adhesive composition for polarizing plates that uses the active energy ray-curable adhesive composition; an adhesive for polarizing plates; and a polarizing plate. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of a polarizing plate according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] As used herein, the following terms have the following meanings: (Meth)acrylate is a general term for methacrylate and acrylate. The (meth)acryloyl group is a general term for a methacryloyl group and an acryloyl group. (Meth)acrylic means a generic term for methacryl and acrylic. The term "substantially free" means that the component is not actively blended in. For example, it means that the component is contained in an amount of less than 1 wt %, particularly less than 0.5 wt %, of the total active energy ray-curable adhesive composition. The symbol "~" indicating a range of values ​​means that the values ​​before and after it are included as the lower and upper limits.

[0017] An embodiment of the present invention will be described in detail below, but these disclose one example of a preferable embodiment.

[0018] <Active energy ray-curable adhesive composition> The active energy ray-curable adhesive composition of the present invention (hereinafter also referred to as "the adhesive composition") contains an epoxy compound (A), an ethylenically unsaturated compound (B), a photopolymerization initiator (C), and a silane coupling agent (D). One of the characteristics of this adhesive composition is that it does not substantially contain an oxetane compound. It is generally known that the inclusion of an oxetane compound improves curability, but in the present invention, it has been discovered that the limited composition exhibits high adhesiveness by achieving a moderate curing state that is not overly cured by not containing oxetane, and thus the composition can be used at a practical level. With this configuration, an adhesive having excellent adhesive strength between a polarizer and a protective film can be obtained, even if the protective film is an acrylic film or a cyclic olefin film. Each component of the adhesive composition will now be described.

[0019] [Epoxy compound (A)] The epoxy compound (A) contains an aliphatic epoxy compound (A1) and an aromatic epoxy compound (A2).

[0020] Examples of the aliphatic epoxy compound (A1) include monofunctional aliphatic epoxy compounds having one epoxy group in the molecule, such as butyl glycidyl ether, 2-ethylhexyl glycidyl ether, allyl glycidyl ether, glycidol, and alcohol glycidyl ethers having 11 to 15 carbon atoms (such as lauryl alcohol glycidyl ether); aliphatic epoxy compounds having two or more epoxy groups in the molecule, such as neopentyl glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane polyglycidyl ether, pentaerythritol polyglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, polybutadiene diglycidyl ether, sorbitol polyglycidyl ether, glycerin polyglycidyl ether, and polyglycerin polyglycidyl ether; etc. These aliphatic epoxy compounds may be used alone or in combination of two or more.

[0021] Among these, from the viewpoints of curability, adhesion, and durability, aliphatic epoxy compounds having two or more epoxy groups in the molecule and having two or more functionalities are preferred, and glycerin polyglycidyl ether, trimethylolpropane polyglycidyl ether, and pentaerythritol polyglycidyl ether are preferred from the viewpoint of curability, and further, trimethylolpropane polyglycidyl ether is preferred from the viewpoint of versatility.

[0022] Examples of the aromatic epoxy compound (A2) include monofunctional aromatic epoxy compounds having one epoxy group in the molecule, such as phenyl glycidyl ether, p-tert-butylphenyl glycidyl ether, p-sec-butylphenyl glycidyl ether, dibromophenyl glycidyl ether, and resorcinol diglycidyl ether; Examples of such aromatic epoxy compounds include difunctional or higher aromatic epoxy compounds having two or more epoxy groups in the molecule, such as phthalic acid diglycidyl ester, terephthalic acid diglycidyl ester, hydroquinone diglycidyl ether, bromobisphenol A diglycidyl ether, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol E type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, novolac type epoxy resin, and biphenyl type epoxy resin. These aromatic epoxy compounds may be used alone or in combination of two or more.

[0023] Among these, aromatic epoxy compounds having two or more epoxy groups in the molecule and having two or more functionalities are preferred from the viewpoints of adhesion and durability, and bisphenol A type epoxy resins, phenol novolac type epoxy resins, and cresol novolac type epoxy resins are particularly preferred from the viewpoints of excellent curability, with bisphenol A type epoxy resins being preferred from the viewpoint of versatility.

[0024] In a preferred embodiment, the aromatic epoxy compound (A2) does not substantially contain bisphenol S type, naphthalene type, or resorcin type aromatic epoxy compounds. If these are contained, the adhesive layer tends to become colored over time, which is undesirable. With this configuration, even if the protective film is an acrylic film or a cyclic olefin film, an adhesive having excellent adhesive strength between the polarizer and the protective film can be easily obtained.

[0025] In a preferred embodiment, the content of the aliphatic epoxy compound (A1) is greater than the content of the aromatic epoxy compound (A2). According to this configuration, even if the protective film is an acrylic film or a cyclic olefin film, an adhesive having excellent adhesive strength between the polarizer and the protective film can be easily obtained.

[0026] The total content of the epoxy compound (A) is preferably 10 to 49.5% by weight, more preferably 20 to 45% by weight, and even more preferably 30 to 40% by weight, based on the total of the epoxy compound (A), the ethylenically unsaturated compound (B), the photopolymerization initiator (C), and the silane coupling agent (D). If the content of the epoxy compound (A) is outside the above range, the balance between the adhesiveness and the durability tends to decrease.

[0027] The content ratio (A1 / A2) of the aliphatic epoxy compound (A1) to the aromatic epoxy compound (A2) is preferably 99 / 1 to 20 / 80, more preferably 80 / 20 to 30 / 70, further preferably 75 / 25 to 40 / 60, and particularly preferably 60 / 40 to 51 / 49, by weight ratio. If the weight ratio is too small, i.e., if the amount of the aromatic epoxy compound (A2) is too large, the adhesive property tends to decrease and the compatibility of the adhesive composition tends to decrease. If the weight ratio is too large, i.e., if the amount of the aliphatic epoxy compound (A1) is too large, the adhesive property also tends to decrease.

[0028] The content of the aliphatic epoxy compound (A1) is preferably 5 to 35% by weight, more preferably 10 to 30% by weight, and even more preferably 15 to 22% by weight, based on the total of the epoxy compound (A), the ethylenically unsaturated compound (B), the photopolymerization initiator (C), and the silane coupling agent (D). If the content of the aliphatic epoxy compound (A1) is too low, the adhesiveness tends to decrease, and if it is too high, the adhesiveness also tends to decrease.

[0029] The content of the aromatic epoxy compound (A2) is preferably 5 to 35% by weight, more preferably 10 to 30% by weight, and even more preferably 15 to 22% by weight, based on the total of the epoxy compound (A), the ethylenically unsaturated compound (B), the photopolymerization initiator (C), and the silane coupling agent (D). If the content of the aromatic epoxy compound (A2) is too low, the adhesiveness tends to decrease, and if it is too high, the adhesiveness also tends to decrease.

[0030] Furthermore, the epoxy compound (A) of the present invention may contain, in addition to the aliphatic epoxy compound (A1) and the aromatic epoxy compound (A2), another epoxy compound (A3). Examples of the other epoxy compounds (A3) include triazine skeleton-containing epoxy compounds.

[0031] The triazine skeleton-containing epoxy compound contains one or more epoxy groups and a triazine skeleton in the molecule. For example, tris(2,3-epoxypropyl)-isocyanurate, tris(3,4-epoxybutyl)-isocyanurate, tris(4,5-epoxypentyl)-isocyanurate, tris(5,6-epoxyhexyl)-isocyanurate, tris(6,7-epoxyheptyl)-isocyanurate, tris(7,8-epoxyoctyl)-isocyanurate, etc. The triazine skeleton-containing epoxy compound may be used alone or in combination of two or more. From the viewpoint of further improving durability (thermal shock resistance), it is also preferable to use a triazine skeleton-containing epoxy compound.

[0032] The epoxy equivalent of the triazine skeleton-containing epoxy compound is preferably 120 g / eq or more, more preferably 120 to 300 g / eq, and even more preferably 120 to 250 g / eq, from the viewpoints of adhesiveness and durability.

[0033] As the triazine skeleton-containing epoxy compound, a commercially available product may be used. For example, the TEPIC series manufactured by Nissan Chemical Industries, Ltd. ("TEPIC-G", "TEPIC-S", "TEPIC-SS", "TEPIC-HP", "TEPIC-L", "TEPIC-PAS", "TEPIC-VL", "TEPIC-UC", "TEPIC-FL", etc.) can be mentioned. Among them, from the viewpoint of compatibility, the liquid epoxy compounds "TEPIC-PAS", "TEPIC-VL", "TEPIC-UC", and "TEPIC-FL" are preferable.

[0034] The content of the other epoxy compound (A3) is preferably 30% by weight or less, more preferably 20% by weight or less, and even more preferably 10% by weight or less, based on the total weight of the epoxy compound (A). If the content of the other epoxy compound (A3) is too high, the adhesive strength tends to decrease.

[0035] [Ethylenically unsaturated compounds (B)] The ethylenically unsaturated compound (B) is an unsaturated compound having at least one ethylenically unsaturated group in the molecule. The ethylenically unsaturated compound (B) is the main component of the adhesive composition. By including the ethylenically unsaturated compound (B), the curing speed can be adjusted and the curing property is improved.

[0036] The ethylenically unsaturated compound (B) is not particularly limited as long as it is, for example, a (meth)acrylic compound having at least one (meth)acryloyl group in the molecule. Examples of the (meth)acrylic compound include (meth)acrylic compounds having one (meth)acryloyl group in the molecule (hereinafter also referred to as "monofunctional"); and (meth)acrylic compounds having two or more (meth)acryloyl groups in the molecule (hereinafter also referred to as "polyfunctional").

[0037] Examples of the (meth)acrylic compound include aliphatic (meth)acrylates, polar group-containing (meth)acrylic compounds, alicyclic (meth)acrylates, aromatic (meth)acrylates, and (meth)acrylates having a (meth)acryloyl group and a reactive functional group other than the (meth)acryloyl group in the molecule.

[0038] As the ethylenically unsaturated compound (B), from the viewpoints of improving the curability and enhancing the adhesive properties of the present adhesive composition, an aliphatic (meth)acrylate (B1) is preferred. As the aliphatic (meth)acrylate, for example, a compound having a hydrocarbon chain with 1 to 20 carbon atoms, particularly 1 to 10, and further 1 to 5 carbon atoms is preferred, and among these, an alkyl (meth)acrylate having an alkyl group or an alkylene group and 1 to 4 carbon atoms is preferred. Specifically, monofunctional aliphatic (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; Bifunctional aliphatic (meth)acrylates such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate; trimethylolpropane tri(meth)acrylate, glycerin and polyfunctional aliphatic (meth)acrylates such as trifunctional or higher aliphatic (meth)acrylates, such as dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, and caprolactone-modified pentaerythritol tetra(meth)acrylate. Other examples of the aliphatic (meth)acrylic compound include alkoxy group-containing (meth)acrylates and oxyalkylene group-containing (meth)acrylates.

[0039] Examples of the alkoxy group-containing (meth)acrylate include monofunctional alkoxyalkyl (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, and 2-butoxyethyl (meth)acrylate; monofunctional polyether chain-containing (meth)acrylates such as 2-butoxydiethylene glycol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polyethylene glycol-polypropylene glycol-mono(meth)acrylate, lauroxypolyethylene glycol mono(meth)acrylate, and stearoxypolyethylene glycol mono(meth)acrylate; and the like.

[0040] Examples of the oxyalkylene group-containing (meth)acrylate include bifunctional oxyalkylene group-containing acrylates such as diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene diglycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and hydroxypivalic acid-modified neopentyl glycol di(meth)acrylate; Tri- or higher functional oxyalkylene group-containing acrylates, such as polyethylene oxide-modified dipentaerythritol hexa(meth)acrylate, polyethylene oxide-modified pentaerythritol tetra(meth)acrylate, and polyethylene oxide-modified glycerin tri(meth)acrylate; and polyfunctional oxyalkylene group-containing acrylates such as those mentioned above.

[0041] Examples of polar group-containing (meth)acrylic compounds include carboxy group-containing (meth)acrylic compounds, hydroxyl group-containing (meth)acrylates, and nitrogen atom-containing (meth)acrylic compounds.

[0042] Examples of the carboxy group-containing (meth)acrylic compound include monofunctional carboxy group-containing (meth)acrylic compounds such as (meth)acrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, fumaric acid, acrylamido-N-glycolic acid, cinnamic acid, Michael adducts of (meth)acrylic acid (e.g., acrylic acid dimer, methacrylic acid dimer, acrylic acid trimer, methacrylic acid trimer, acrylic acid tetramer, methacrylic acid tetramer, etc.), and 2-(meth)acryloyloxyethyl dicarboxylic acid monoesters (e.g., 2-acryloyloxyethyl succinic acid monoester, 2-methacryloyloxyethyl succinic acid monoester, 2-acryloyloxyethyl phthalic acid monoester, 2-methacryloyloxyethyl phthalic acid monoester, 2-acryloyloxyethyl hexahydrophthalic acid monoester, 2-methacryloyloxyethyl hexahydrophthalic acid monoester, etc.).

[0043] Examples of hydroxyl group-containing (meth)acrylates include primary hydroxyl group-containing (meth)acrylates, secondary hydroxyl group-containing (meth)acrylates, and tertiary hydroxyl group-containing (meth)acrylates.

[0044] Examples of the primary hydroxyl group-containing (meth)acrylate include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate; Caprolactone-modified (meth)acrylates such as caprolactone-modified 2-hydroxyethyl (meth)acrylate; Mono(meth)acrylates of dihydric alcohols, such as ethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate, pentanediol mono(meth)acrylate, and hexanediol mono(meth)acrylate; Mono(meth)acrylate of diethylene glycol, mono(meth)acrylate of triethylene glycol; mono(meth)acrylates of polyalkylene glycols, such as mono(meth)acrylate of tetraethylene glycol, mono(meth)acrylate of polyethylene glycol, mono(meth)acrylate of dipropylene glycol, mono(meth)acrylate of tripropylene glycol, and mono(meth)acrylate of polypropylene glycol; Monofunctional primary hydroxyl group-containing (meth)acrylates such as 2-acryloyloxyethyl-2-hydroxyethyl phthalate; Bifunctional primary hydroxyl group-containing (meth)acrylates such as pentaerythritol di(meth)acrylate; trifunctional or higher primary hydroxyl group-containing (meth)acrylates such as pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, and ethylene oxide-modified pentaerythritol tri(meth)acrylate; and other multifunctional primary hydroxyl group-containing (meth)acrylates; etc.

[0045] Examples of the secondary hydroxyl group-containing (meth)acrylate include monofunctional secondary hydroxyl group-containing (meth)acrylates such as 2-hydroxypropyl (meth)acrylate and 2-hydroxybutyl (meth)acrylate; and polyfunctional secondary hydroxyl group-containing (meth)acrylates such as bifunctional secondary hydroxyl group-containing (meth)acrylates such as glycerin di(meth)acrylate.

[0046] Examples of the tertiary hydroxyl group-containing (meth)acrylate include monofunctional tertiary hydroxyl group-containing (meth)acrylates such as 2,2-dimethyl 2-hydroxyethyl (meth)acrylate.

[0047] Further, examples of hydroxyl group-containing (meth)acrylates other than those mentioned above include tri- or higher functional hydroxyl group-containing (meth)acrylates such as polyglycerin poly(meth)acrylate.

[0048] Examples of the nitrogen atom-containing (meth)acrylic compound include amide group-containing (meth)acrylic compounds, amino group-containing (meth)acrylic compounds, and other nitrogen atom-containing (meth)acrylic compounds.

[0049] Examples of the amide group-containing (meth)acrylic compound include N,N-dialkyl (meth)acrylamides such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, and N,N-diethyl (meth)acrylamide; N-alkoxyalkyl (meth)acrylamides such as N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, N-propoxymethyl (meth)acrylamide, N-isopropoxymethyl (meth)acrylamide, Nn-butoxymethyl (meth)acrylamide, and N-isobutoxymethyl (meth)acrylamide; hydroxyl group-containing acrylamide such as N-(hydroxymethyl) (meth)acrylamide; monofunctional amide group-containing (meth)acrylic compounds such as N-(3-N,N-dimethylaminopropyl) (meth)acrylamide, methylene bis (meth)acrylamide, ethylene bis (meth)acrylamide, and acryloylmorpholine; Bifunctional amide group-containing (meth)acrylic compounds such as isocyanuric acid ethylene oxide modified di(meth)acrylate; etc.

[0050] Examples of the amino group-containing (meth)acrylic compound include primary amino group-containing (meth)acrylates such as aminomethyl (meth)acrylate, aminoethyl (meth)acrylate, and aminoalkyl (meth)acrylate; secondary amino group-containing (meth)acrylates such as ethylaminoethyl (meth)acrylate and t-butylaminoethyl (meth)acrylate; and tertiary amino group-containing (meth)acrylates such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and dialkylaminoalkyl (meth)acrylate; and other monofunctional amino group-containing (meth)acrylic compounds.

[0051] Examples of the alicyclic (meth)acrylate include monofunctional alicyclic (meth)acrylate compounds such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, 1,4-cyclohexanedimethylol mono(meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and 2-adamantyl (meth)acrylate; and bifunctional alicyclic (meth)acrylate compounds such as cyclohexanedimethanol di(meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, and ethylene oxide-modified cyclohexanedimethanol di(meth)acrylate.

[0052] Examples of aromatic (meth)acrylates include phenoxyalkyl (meth)acrylates such as phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenoxypropyl (meth)acrylate; phenoxydiethylene glycol (meth)acrylate, phenoxydipropylene glycol (meth)acrylate, and other phenoxydialkylene glycol (meth)acrylates; phenoxypolyethylene glycol (meth)acrylate, phenoxypolyethylene glycol-polypropylene glycol (meth)acrylate, p-cumylphenol alkylene oxide adduct (meth)acrylate, o-phenylphenol alkylene oxide adduct (meth)acrylate, phenol alkylene oxide adduct (meth)acrylate, and nonylphenol alkylene oxide adduct (meth)acrylate, and other monofunctional aromatic (meth)acrylate-based compounds; Alkylene oxide modified bisphenol A di(meth)acrylates such as ethylene oxide modified bisphenol A di(meth)acrylate and propylene oxide modified bisphenol A di(meth)acrylate; bifunctional aromatic (meth)acrylate compounds such as bisphenol A diglycidyl ether di(meth)acrylate and phthalic acid diglycidyl ester di(meth)acrylate; and polyfunctional aromatic (meth)acrylates such as these; etc.

[0053] Examples of (meth)acrylic compounds having a (meth)acryloyl group and a reactive functional group other than a (meth)acryloyl group in the molecule include monofunctional epoxy group-containing (meth)acrylate compounds such as glycidyl methacrylate, 4-hydroxybutyl acrylate glycidyl ether, and 3,4-epoxycyclohexylmethyl (meth)acrylate; monofunctional vinyl group-containing (meth)acrylate compounds such as 2-(2-vinyloxyethoxy)ethyl (meth)acrylate; and monofunctional isocyanate group-containing (meth)acrylate compounds such as 2-(meth)acryloyloxyethyl isocyanate. Here, when the ethylenically unsaturated compound is an epoxy group-containing (meth)acrylate, it is included in the ethylenically unsaturated compound (B) and is not included in the epoxy compound (A).

[0054] Other examples of the monofunctional (meth)acrylic compound include (meth)acrylate compounds having a cyclic ether structure, such as tetrahydrofurfuryl (meth)acrylate and caprolactone-modified tetrahydrofurfuryl (meth)acrylate. Furthermore, oligomers such as urethane (meth)acrylate, polyester (meth)acrylate, and epoxy (meth)acrylate can also be used as the (meth)acrylic compound.

[0055] Among these, as the ethylenically unsaturated compound (B), a difunctional aliphatic (meth)acrylate is preferred because it is capable of obtaining a fast curing rate and adhesiveness, and a linear difunctional aliphatic (meth)acrylate having an alkylene chain with 1 to 5 carbon atoms, such as 1,4-butanediol di(meth)acrylate, is particularly preferred.

[0056] In a preferred embodiment, the content of the ethylenically unsaturated compound (B) is greater than the content of the epoxy compound (A). According to this configuration, an adhesive having excellent adhesive strength, particularly between an acrylic film and a polarizer, can be easily obtained.

[0057] The content of the ethylenically unsaturated compound (B) is preferably 40% by weight or more, more preferably 50% by weight or more, and even more preferably 55% by weight or more, based on the total of the epoxy compound (A), the ethylenically unsaturated compound (B), the photopolymerization initiator (C), and the silane coupling agent (D). The upper limit of the content of the ethylenically unsaturated compound (B) is usually 90% by weight. If the content of the ethylenically unsaturated compound (B) is too low, the curing speed decreases and adhesive strength tends to be insufficient. If the content of the ethylenically unsaturated compound (B) is too high, curing shrinkage increases and adhesive strength tends to decrease.

[0058] [Photopolymerization initiator (C)] When the adhesive composition is irradiated with active energy rays, the epoxy compound (A), the ethylenically unsaturated compound (B) and the photopolymerization initiator (C) react with each other, thereby exerting adhesive properties. The photopolymerization initiator (C) contains a photocationic polymerization initiator (C1) and a photoradical polymerization initiator (C2). Since the adhesive composition contains a cationic curing component and a radical curing component, sufficient curing properties can be obtained by using the photocationic polymerization initiator (C1) and the photoradical polymerization initiator (C2) in combination as the photopolymerization initiator (C).

[0059] By using the cationic photopolymerization initiator (C1), the adhesive composition can be cured at room temperature (25°C ± 10°C), and the protective film and the polarizer can be well bonded together. The photocationic polymerization initiator (C1) is not particularly limited as long as it is a compound that generates a cationic species or a Lewis acid upon irradiation with active energy rays. Examples of the photocationic polymerization initiator (C1) include onium salts such as aromatic diazonium salts, aromatic iodonium salts, and aromatic sulfonium salts, and iron-allene complexes.

[0060] Examples of aromatic diazonium salts include benzenediazonium hexafluoroantimonate, benzenediazonium hexafluorophosphate, and benzenediazonium hexafluoroborate.

[0061] Examples of aromatic iodonium salts include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and di(4-nonylphenyl)iodonium hexafluorophosphate.

[0062] Examples of aromatic sulfonium salts include triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate, 4,4'-bis[diphenylsulfonio]diphenylsulfide bishexafluorophosphate, 4,4'-bis[di(β-hydroxyethoxy)phenylsulfonio]diphenylsulfide bishexafluoroantimonate, and 4,4'-bis[di(β-hydroxyethoxy)phenylsulfonio]diphenylsulfide bishexafluorophore. phosphate, 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone·hexafluoroantimonate, 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone·tetrakis(pentafluorophenyl)borate, 4-phenylcarbonyl-4'-diphenylsulfonio-diphenylsulfide·hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4'-diphenylsulfonio-diphenylsulfide·hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4'-di(p-toluyl)sulfonio-diphenylsulfide·tetrakis(pentafluorophenyl)borate, etc.

[0063] Examples of iron-arene complexes include xylene-cyclopentadienyliron(II)-hexafluoroantimonate, cumene-cyclopentadienyliron(II)-hexafluorophosphate, and xylene-cyclopentadienyliron(II)-tris(trifluoromethylsulfonyl)methanide.

[0064] Among the photocationic polymerization initiators (C1), aromatic iodonium salts and aromatic sulfonium salts are preferred because they react with high sensitivity to light sources of long wavelengths, aromatic sulfonium salts are particularly preferred, and diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate is especially preferred. The cationic photopolymerization initiator (C1) may be used alone or in combination of two or more kinds.

[0065] The photoradical polymerization initiator (C2) generates radicals when irradiated with active energy rays, and reacts with the ethylenically unsaturated compound (B). Examples of the photoradical polymerization initiator (C2) include acetophenones such as diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, and 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomer; benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; Benzophenones such as benzophenone, o-benzoylbenzoic acid methyl, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propenyloxy)ethyl]benzenemethanaminium bromide, and (4-benzoylbenzyl)trimethylammonium chloride; Thioxanthones such as 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, and 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one mesochloride; Acylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; Oxime esters such as 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime); and the like.

[0066] Among these photoradical polymerization initiators (C2), acylphosphine oxides are preferred, particularly 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide are preferred, further 2,4,6-trimethylbenzoyl-phenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide are preferred, and particularly bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide is preferred.

[0067] As an auxiliary for the photoradical polymerization initiator (C2), it is also possible to use triethanolamine, triisopropanolamine, 4,4'-dimethylaminobenzophenone (Michler's ketone), 4,4'-diethylaminobenzophenone, 2-dimethylaminoethylbenzoic acid, ethyl 4-dimethylaminobenzoate, (n-butoxy)ethyl 4-dimethylaminobenzoate, isoamyl 4-dimethylaminobenzoate, 2-ethylhexyl 4-dimethylaminobenzoate, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, etc. in combination.

[0068] In order to obtain sufficient curability, the content of the photopolymerization initiator (C) is preferably 1 to 20 parts by weight, particularly preferably 2 to 15 parts by weight, and even more particularly preferably 3 to 10 parts by weight, based on 100 parts by weight in total of the epoxy compound (A) and the ethylenically unsaturated compound (B). If the content of the photopolymerization initiator (C) is too low, the curability will decrease and the mechanical strength and adhesive strength will tend to decrease, whereas if the content is too high, the solubility of the photopolymerization initiator (C) itself in the composition will tend to decrease.

[0069] The content of the cationic photopolymerization initiator (C1) is preferably 1 to 20 parts by weight, more preferably 2 to 15 parts by weight, and even more preferably 3 to 10 parts by weight, based on 100 parts by weight of the total amount of the epoxy compound (A) and the ethylenically unsaturated compound (B). If the content of the cationic photopolymerization initiator (C1) is too high, the solubility and durability tend to decrease, while if the content is too low, the curability and adhesive strength tend to decrease.

[0070] The content of the photoradical polymerization initiator (C2) is less than 1 part by weight per 100 parts by weight of the total of the epoxy compound (A) and the ethylenically unsaturated compound (B). In particular, 0.8 parts by weight or less is preferable, and 0.6 parts by weight or less is particularly preferable. If the content of the photoradical polymerization initiator (C2) is too high, the solubility of the photoradical polymerization initiator (C2) tends to decrease, and the durability of the adhesive layer tends to decrease. Usually, the lower limit of the content of the photoradical polymerization initiator (C2) is 0.1 parts by weight. If the content is too small, the curability tends to decrease and the adhesive strength of the adhesive layer tends to decrease.

[0071] In particular, from the viewpoint of curing efficiency, i.e., efficient curing with a small amount of irradiation of active energy rays, a preferred combination of the photocationic polymerization initiator (C1) and the photoradical polymerization initiator (C2) is to use an aromatic sulfonium salt as the photocationic polymerization initiator (C1) and an acylphosphine oxide as the photoradical polymerization initiator (C2).

[0072] [Silane coupling agent (D)] The adhesive composition contains a silane coupling agent (D) to improve adhesion. The silane coupling agent (D) is usually an organosilicon compound containing one or more reactive functional groups and one or more silicon-bonded alkoxy groups in its structure. The silane coupling agent (D) can improve the adhesion between the adhesive layer and the protective film.

[0073] Examples of the silane coupling agent (D) include epoxy group-containing silane coupling agents, mercapto group-containing silane coupling agents, (meth)acryloyl group-containing silane coupling agents, amino group-containing silane coupling agents, isocyanate group-containing silane coupling agents, vinyl group-containing silane coupling agents, hydroxyl group-containing silane coupling agents, carboxyl group-containing silane coupling agents, and amide group-containing silane coupling agents. The silane coupling agent (D) may be used alone or in combination of two or more kinds.

[0074] Examples of epoxy group-containing silane coupling agents include glycidyloxy group (aliphatic epoxy group)-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropylmethyldimethoxysilane; monomeric epoxy group-containing silane coupling agents such as alicyclic epoxy group-containing silane coupling agents such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; and oligomeric silane coupling agents in which a silane compound is partially hydrolyzed or a silane compound is co-condensed with an alkyl group-containing silane compound such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, or ethyltrimethoxysilane. The epoxy group-containing silane coupling agents may be used alone or in combination of two or more kinds. Here, when the silane coupling agent contains an epoxy group, it is included in the silane coupling agent (D) and is not included in the epoxy compound (A).

[0075] Examples of the mercapto group-containing silane coupling agent include monomeric mercapto group-containing silane coupling agents such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, γ-mercaptopropyldimethoxymethylsilane, and 3-mercaptopropylmethyldimethoxysilane; and oligomeric silane coupling agents in which a silane compound is partially hydrolyzed or a silane compound and an alkyl group-containing silane compound such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane are co-condensed. The mercapto group-containing silane coupling agents may be used alone or in combination of two or more kinds.

[0076] Examples of the (meth)acryloyl group-containing silane coupling agent include 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane. The (meth)acryloyl group-containing silane coupling agents may be used alone or in combination of two or more kinds. When the silane coupling agent contains a (meth)acryloyl group, it is included in the silane coupling agent (D) and is not included in the ethylenically unsaturated compound (B).

[0077] Examples of amino group-containing silane coupling agents include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, and N-phenyl-3-aminopropyltrimethoxysilane. The amino group-containing silane coupling agents may be used alone or in combination of two or more kinds.

[0078] Examples of the isocyanate group-containing silane coupling agent include 3-isocyanate propyl triethoxy silane, etc. The isocyanate group-containing silane coupling agents may be used alone or in combination of two or more kinds.

[0079] Examples of the vinyl group-containing silane coupling agent include vinyltrimethoxysilane, vinyltriethoxysilane, etc. The vinyl group-containing silane coupling agent may be used alone or in combination of two or more kinds. Here, when the silane coupling agent contains a vinyl group, it is included in the silane coupling agent (D) and is not included in the ethylenically unsaturated compound (B).

[0080] Among the silane coupling agents (D), it is preferable to use an epoxy group-containing silane coupling agent, a vinyl group-containing silane coupling agent, or a (meth)acryloyl group-containing silane coupling agent, because of their excellent reactivity with the cationic polymerization component [epoxy compound (A)] and the radical polymerization component [ethylenically unsaturated compound (B)], and particularly preferably an epoxy group-containing silane coupling agent or a (meth)acryloyl group-containing silane coupling agent. In addition, the silane coupling agent (D) may be either a monomer-type silane coupling agent or an oligomer-type silane coupling agent that is partially hydrolyzed and polycondensed, but it is preferable to use a monomer-type silane coupling agent from the viewpoint of compatibility and adhesiveness. Particularly preferred is 3-glycidoxypropyltrimethoxysilane.

[0081] The content of the silane coupling agent (D) is preferably 0.05 to 2 parts by weight, particularly preferably 0.1 to 1 part by weight, and further preferably 0.3 to 0.8 parts by weight, per 100 parts by weight of the total of the epoxy compound (A) and the ethylenically unsaturated compound (B). If the content of the silane coupling agent (D) is too high, the liquid stability and the durability (thermal shock resistance) after curing tend to decrease, while if the content is too low, the effect of further improving the adhesiveness tends not to be obtained sufficiently.

[0082] [Other ingredients] The adhesive composition may further contain components other than the epoxy compound (A), the ethylenically unsaturated compound (B), the photopolymerization initiator (C), and the silane coupling agent (D) within the range that does not impair the effects of the present invention. Other components may include, for example, photosensitizers, polyols, antistatic agents, other adhesives, acrylic resins, urethane resins, rosins, rosin esters, hydrogenated rosin esters, phenolic resins, aromatic modified terpene resins, aliphatic petroleum resins, alicyclic petroleum resins, styrene resins, xylene resins, and other additives such as plasticizers, colorants, fillers, antioxidants, ultraviolet absorbers, and functional dyes, as well as compounds that change color or undergo discoloration when exposed to ultraviolet light or radiation. The amount of each of these additives is appropriately set for each additive. For example, the total amount of additives is preferably 30% by weight or less of the total amount of the adhesive composition, and particularly preferably 20% by weight or less. In addition to the additives described above, the adhesive composition may contain small amounts of impurities contained in the raw materials used to produce the constituent components.

[0083] For example, the use of a photosensitizer can improve reactivity and the mechanical strength and adhesive strength of the cured product. Examples of photosensitizers include anthracene derivatives such as 9,10-dibutoxyanthracene and 9,10-diethoxyanthracene; benzoin derivatives such as benzoin methyl ether, benzoin isopropyl ether, and α,α-dimethoxy-α-phenylacetophenone; benzophenone derivatives such as benzophenone, 2,4-dichlorobenzophenone, methyl o-benzoylbenzoate, 4,4'-bis(dimethylamino)benzophenone, and 4,4'-bis(diethylamino)benzophenone; carbonyl compounds such as anthraquinone derivatives such as 2-chloroanthraquinone and 2-methylanthraquinone; organic sulfur compounds such as thioxanthone derivatives such as 2-chlorothioxanthone, 2-isopropylthioxanthone, and 2,4-diethylthioxanthen-9-one; persulfides; redox compounds; azo compounds; diazo compounds; halogen compounds; and photoreducible dyes. These may be used alone or in combination of two or more. Among these, anthracene derivatives and thioxanthone derivatives are preferred.

[0084] The photosensitizer is preferably contained in an amount of 0.01 to 20 parts by weight based on 100 parts by weight of the photopolymerization initiator (C). If the content of the photosensitizer is too high, the adhesive composition and the resulting adhesive layer tend to be colored, whereas if the content is too low, the reactivity tends to decrease and the sensitizing effect tends not to be obtained.

[0085] [Manufacturing method] The adhesive composition of the present invention can be obtained by blending and mixing the respective components in a predetermined ratio. The adhesive composition of the present invention may be used as it is as an adhesive composition for polarizing plates.

[0086] <Adhesive for polarizing plates> The adhesive for polarizing plates of the present invention is a cured product of the adhesive composition for polarizing plates, and therefore has excellent adhesive strength between the polarizer and the protective film. As described above, the adhesive composition of the present invention becomes an adhesive by being cured by irradiation with active energy rays, and therefore can be suitably used as an adhesive for polarizing plates for bonding a polarizer and a protective film.

[0087] Furthermore, in the present invention, the film has good adhesion not only to TAC films which have been commonly used as protective films for polarizers, but also to protective films such as acrylic films, cyclic olefin films, and PET films which have previously shown poor adhesion to polarizers made of PVA films.

[0088] However, in addition to its use as an adhesive for polarizing plates, the adhesive composition can also be used, for example, for bonding various optical films or sheets, and for bonding electronic parts, precision instruments, packaging materials, display materials, and the like.

[0089] <Polarizing plate> The polarizing plate of the present invention is formed by bonding a polarizer and a protective film via a polarizing plate adhesive. The polarizing plate according to one embodiment has a polarizer, a protective film, and an adhesive layer for bonding the polarizer and the protective film together, the adhesive layer being made of the polarizing plate adhesive of the present invention. For example, a protective film is bonded to at least one surface, preferably both surfaces, of a polarizer using the polarizing plate adhesive of the present invention. Typically, the liquid adhesive composition of the present invention is uniformly applied to one or both bonding surfaces of the polarizer and the protective film, and then the two are bonded together, pressed together, and irradiated with active energy rays to obtain a polarizing plate.

[0090] As the polarizer, a uniaxially stretched film dyed with an aqueous solution of iodine-potassium iodide or a dichroic dye using a film made of a PVA-based resin as a raw film is usually used. The average polymerization degree of the PVA-based resin is preferably 1,500 to 10,000. The saponification degree of the PVA-based resin is preferably 85 to 100 mol%, more preferably 95 to 100 mol%. The stretching ratio is usually 2 to 10 times, preferably about 3 to 7 times.

[0091] PVA-based resins are usually produced by saponifying polyvinyl acetate obtained by polymerizing vinyl acetate. Such PVA-based resins may contain small amounts of components copolymerizable with vinyl acetate, such as unsaturated carboxylic acids (including salts, esters, amides, nitriles, etc.), olefins, vinyl ethers, unsaturated sulfonates, etc. In addition, PVA-based resins also include so-called polyvinyl acetal resins and PVA derivatives, such as polybutyral resins and polyvinyl formal resins, which are produced by reacting PVA with aldehydes in the presence of an acid.

[0092] The protective film of the polarizing plate is not particularly limited. In addition to the conventional TAC-based film, acrylic films, polyethylene films, polypropylene films, cyclic olefin films, etc. can also be used, and the adhesive composition of the present invention can be suitably used for any protective film selected from the TAC-based film, acrylic film, cyclic olefin film, polyethylene terephthalate (PET) film, etc.

[0093] When applying the adhesive composition onto a polarizer or a protective film, for example, a reverse coater, a gravure coater (direct, reverse, offset), a bar reverse coater, a roll coater, a die coater, a bar coater, a rod coater, etc. can be used, or application can be performed by a dipping method.

[0094] When laminating or pressing, for example, a roll laminator or the like can be used, and the pressure is usually selected from the range of 0.1 to 10 MPa.

[0095] Examples of the active energy rays that can be used include light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, and infrared rays, electromagnetic waves such as X-rays and γ-rays, as well as electron beams, proton beams, neutron beams, etc. In view of the curing speed, availability of irradiation equipment, cost, etc., ultraviolet rays are preferred.

[0096] Examples of light sources that can be used for ultraviolet irradiation include high-pressure mercury lamps, electrodeless lamps, extra-high-pressure mercury lamps, carbon arc lamps, xenon lamps, metal halide lamps, chemical lamps, black lights, and LED lamps. UV irradiation is usually 50 to 2,000 mJ / cm 2 , preferably 100 to 1,000 mJ / cm 2 , and more preferably 200 to 600 mJ / cm 2 This is carried out under the following conditions. The irradiation time of ultraviolet light varies depending on the type of light source, the distance between the light source and the coating surface, the coating thickness, and other conditions, but is usually several seconds to several tens of seconds, and in some cases may be as little as a fraction of a second.

[0097] The active energy rays can be irradiated from any appropriate direction, but from the viewpoint of preventing deterioration of the polarizer, it is preferable to irradiate from the transparent protective film side.

[0098] The thickness of the adhesive layer in the polarizing plate can be usually 0.1 to 10 μm, preferably 0.2 to 5 μm, more preferably 0.5 to 4 μm, and even more preferably 1 to 3 μm. If the thickness is too thin, the adhesive itself does not have sufficient cohesive force, and the adhesive strength tends not to be sufficient, whereas if the thickness is too thick, the processability of the polarizing plate tends to decrease due to cracks during punching, etc.

[0099] Fig. 1 is a cross-sectional view showing a schematic example of a polarizing plate. The polarizing plate 1 shown in Fig. 1 has a polarizer 2, adhesive layers 3, 3, a first protective film 4, and a second protective film 5. In this example, the adhesive layers 3, 3 are provided on both sides of the polarizer 2, the first protective film 4 is bonded to the polarizer 2 by one adhesive layer 3, and the second protective film 5 is bonded to the polarizer 2 by the other adhesive layer 3. The first protective film 4 and the second protective film 5 may be made of the same material or different materials. However, the polarizing plate of the present invention is not limited to the example shown in Fig. 1, and may have a configuration in which a protective film is provided only on one side of the polarizer 2. The dimensional ratio in Fig. 1 is for the sake of convenience of explanation and may differ from the actual ratio.

[0100] The adhesive composition can be used for various adhesive applications, and is particularly suitable for bonding various polarizing plate protective films to polarizers, and exhibits extremely excellent adhesive properties. EXAMPLES

[0101] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" are by weight.

[0102] Prior to the Examples and Comparative Examples, the components of the adhesive composition shown below were prepared.

[0103] [Epoxy compound (A)] [Aliphatic epoxy compound (A1)] (A1-1): Trimethylolpropane triglycidyl ether: "Denacol EX-321" manufactured by Nagase ChemteX Corporation) [Aromatic epoxy compound (A2)] (A2-1): Bisphenol A type epoxy resin ("jER-828" manufactured by Mitsubishi Chemical Corporation)

[0104] [Ethylenically unsaturated compounds (B)] [Polyfunctional aliphatic (meth)acrylate (B1)] (B1-1): 1,4-butanediol diacrylate (aliphatic acrylate having two acryloyl groups in the molecule: MIWON "MIRAMER M204") (B1-2): 1,6-hexanediol diacrylate (aliphatic acrylate having two acryloyl groups in the molecule: "Light Acrylate 1.6HX-A" manufactured by Kyoeisha Chemical Co., Ltd.)

[0105] [Photopolymerization initiator (C)] [Photocationic polymerization initiator (C1)] (C1-1): Diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate (aromatic sulfonium salt: San-Apro "CPI-100P") [Photoradical polymerization initiator (C2)] (C2-1): Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (IGM Resins "Omnirad819")

[0106] [Silane coupling agent (D)] (D-1): Epoxy group-containing silane coupling agent ("KBM-403 (3-glycidoxypropyltrimethoxysilane)" manufactured by Shin-Etsu Chemical Co., Ltd.)

[0107] [Oxetane Compounds] Toagosei "Aron Oxetane OXT-221"

[0108] <Examples 1 to 4 and Comparative Examples 1 to 3> [Preparation of adhesive composition] The components were blended in the blending ratios shown in Table 1 below, and mixed to prepare an adhesive composition.

[0109] [Table 1]

[0110] In Table 1, the amounts of the photopolymerization initiator (C) and the silane coupling agent (D) are based on 100 parts by weight of the total of the epoxy compound (A) and the ethylenically unsaturated compound (B). The contents of the epoxy compound (A) and the ethylenically unsaturated compound (B) in each adhesive composition are shown in Table 2, converted into values ​​when the total of the epoxy compound (A), the ethylenically unsaturated compound (B), the photopolymerization initiator (C) and the silane coupling agent (D) is taken as 100% by weight. Furthermore, for the ethylenically unsaturated compound (B) in each adhesive composition example, Table 3 shows the value converted into the compounding ratio when the total amount of the epoxy compound (A) is taken as 100 parts by weight.

[0111] [Table 2]

[0112] [Table 3]

[0113] [Preparation of polarizer] First, a PVA film with a thickness of 60 μm was stretched 1.5 times while immersed in a water bath with a water temperature of 30° C. Next, the film was stretched 1.3 times while immersed in a dyeing bath containing an aqueous solution (liquid temperature 30° C.) with an iodine concentration of 0.2 g / L and a potassium iodide concentration of 15 g / L for 240 seconds. Furthermore, the film was immersed in a boric acid treatment bath containing an aqueous solution (liquid temperature 50° C.) with a boric acid concentration of 50 g / L and a potassium iodide concentration of 30 g / L, and was simultaneously uniaxially stretched 3.08 times while being boric acid treated for 5 minutes. After that, the film was dried at 90° C. to produce a polarizer with a total stretch ratio of 6 times.

[0114] [Preparation of polarizing plate test piece (I)] A cyclic olefin film having a thickness of 40 μm and an acrylic film having a thickness of 40 μm were prepared as protective films having a size of 200 mm×150 mm. The adhesive composition of each example was applied to each of these protective films with a bar coater to a thickness of 2.5 μm to obtain a film with the adhesive composition. Then, each film with the adhesive composition layer was laminated on both sides of a polarizer having a size of 180 mm×120 mm, and the films were laminated with a nip pressure of 1.5 MPa using a roller to obtain a laminated film (1) (layer structure of the laminated film: cyclic olefin film / adhesive composition layer / polarizer / adhesive composition layer / acrylic film).

[0115] Next, the laminated film (1) was irradiated from the cyclic olefin film side with an ultraviolet ray irradiation device equipped with an electrodeless lamp, with a peak irradiance of 440 mW / cm 2 , Accumulative exposure: 400mJ / cm 2 The adhesive composition was cured by irradiation with ultraviolet light using a UV illuminometer (UVA value on a UV POWERPUCK II), to prepare a polarizing plate test piece (I).

[0116] [Measurement and evaluation of adhesive strength] One day after UV irradiation, the polarizing plate test piece [II] was cut to 120 mm x 25 mm, and the adhesive strength between the cyclic olefin film and the polarizer, and the adhesive strength between the acrylic film on the other side and the polarizer were measured when a stress was applied in a 90° direction. A Texture Analyzer manufactured by Eiko Seiki Co., Ltd. was used to measure the adhesive strength.

[0117] The adhesive strength was evaluated according to the following criteria, and the results are shown in Table 4 below. ◎: Adhesive strength is 2.0N / 25mm or more. ◯: The adhesive strength is 1.4 N / 25 mm or more and less than 2.0 N / 25 mm. ×: The adhesive strength is less than 1.4 N / 25 mm.

[0118] [Table 4]

[0119] *In Table 4, a "z" next to the adhesive strength value indicates that zipping was observed in that example.

[0120] In Examples 1 to 4, which are within the scope of the active energy ray-curable adhesive composition of the present invention, excellent adhesion was achieved to both the cyclic olefin-based and acrylic-based protective films. In contrast, in Comparative Example 1 in which an oxetane compound was contained, the adhesive strength was low both to the cyclic olefin-based film and to the acrylic-based film. In Comparative Example 2, in which the content of the photoradical initiator (C2) was high, the adhesive strength to the acrylic film was excellent, but the adhesive strength to the cyclic olefin film was low. Comparative Example 3, which did not contain a silane coupling agent, also had excellent adhesive strength to acrylic films, but had poor adhesive strength to cyclic olefin films. [Industrial Applicability]

[0121] The active energy ray-curable adhesive composition of the present invention and the polarizing plate adhesive composition comprising the active energy ray-curable adhesive composition have excellent adhesion between a polarizer and a protective film, and are suitable for bonding various polarizing plate protective films to a polarizer. Furthermore, they are excellent in terms of curability, adhesion, and durability in a well-balanced manner. The active energy ray-curable adhesive composition of the present invention can be used not only as an adhesive for polarizing plates, but also for laminating various optical films or sheets, electronic components, precision instruments, packaging materials, display materials, etc. [Explanation of symbols]

[0122] 1...polarizing plate, 2...polarizer, 3...adhesive layer, 4...first protective film, 5...second protective film.

Claims

1. An active energy ray-curable adhesive composition comprising an epoxy compound (A), an ethylenically unsaturated compound (B), a photopolymerization initiator (C), and a silane coupling agent (D), The active energy ray-curable adhesive composition is substantially free of an oxetane compound, The epoxy compound (A) contains an aliphatic epoxy compound (A1) and an aromatic epoxy compound (A2), the photopolymerization initiator (C) contains a photocationic polymerization initiator (C1) and a photoradical polymerization initiator (C2); the content of the aliphatic epoxy compound (A1) is 5 to 35% by weight based on the total content of the epoxy compound (A), the ethylenically unsaturated compound (B), the photopolymerization initiator (C), and the silane coupling agent (D); the content of the aromatic epoxy compound (A2) is 5 to 35% by weight based on the total content of the epoxy compound (A), the ethylenically unsaturated compound (B), the photopolymerization initiator (C), and the silane coupling agent (D); the content of the ethylenically unsaturated compound (B) is 40 to 90% by weight based on the total content of the epoxy compound (A), the ethylenically unsaturated compound (B), the photopolymerization initiator (C), and the silane coupling agent (D); the content of the photocationic polymerization initiator (C1) is 1 to 20 parts by weight based on 100 parts by weight of the total amount of the epoxy compound (A) and the ethylenically unsaturated compound (B); the content of the photoradical polymerization initiator (C2) is 0.1 parts by weight or more and less than 1 part by weight, relative to 100 parts by weight in total of the epoxy compound (A) and the ethylenically unsaturated compound (B).

2. 2. The active energy ray-curable adhesive composition according to claim 1, wherein the content of the aliphatic epoxy compound (A1) is greater than the content of the aromatic epoxy compound (A2).

3. 3. The active energy ray-curable adhesive composition according to claim 1, wherein the aromatic epoxy compound (A2) is substantially free of bisphenol S type, naphthalene type, or resorcin type aromatic epoxy compounds.

4. The active energy ray-curable adhesive composition according to any one of claims 1 to 3, wherein the ethylenically unsaturated compound (B) is an alkyl (meth)acrylate having 1 to 4 carbon atoms.

5. The active energy ray-curable adhesive composition according to any one of claims 1 to 4, wherein the content of the ethylenically unsaturated compound (B) is greater than the content of the epoxy compound (A).

6. An adhesive composition for polarizing plates, comprising the active energy ray-curable adhesive composition according to any one of claims 1 to 5.

7. An adhesive for polarizing plates, which is a cured product of the adhesive composition for polarizing plates according to claim 6 .

8. The polarizer includes a polarizer, a protective film, and an adhesive layer that bonds the polarizer and the protective film together, A polarizing plate, wherein the adhesive layer comprises the adhesive for polarizing plates according to claim 7.

9. 9. The polarizing plate according to claim 8, wherein the protective film is at least one selected from the group consisting of an acetyl cellulose film, an acrylic film, a cyclic olefin film, and a polyethylene terephthalate film.

Citation Information

Patent Citations

  • Adhesive for polarizing plate

    JP2014037477A

  • polarizing plate

    JP2014524596A

  • Polarizer, polarizer manufacturing method, polarizing plate including polarizer, and optical display device including polarizing plate

    JP2015129936A

  • Curable composition, manufacturing method of cured article and the cured article

    JP2017179161A

  • Active-energy ray curable adhesive composition, adhesive composition for polarizing plate, adhesive for polarizing plate, and polarizing plate using the same

    JP2020105265A